2019
DOI: 10.1186/s42269-019-0239-y
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and meat quality of commercial Cobb chicken fed diets containing different levels of prickly pear fruits (Opuntia ficus indica) peel

Abstract: Background: The objective of this study was to determine the impacts arising from the substitution of prickly pear fruits (Opuntia ficus indica) peels at different levels (0, 5, 10, and 15%) with yellow corn grain in broiler diets and meat quality. In this study, 200 male chick of commercial Cobb breed were used to study the effect of partially replacing of yellow corn grain (YC) with prickly pear fruits peel powder (PPP). Chicks were divided into four treatments (50 birds each), each treatment contained 5 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…The incorporation of FB g seed husks and seed cakes at a rate of 10% and 20% in the feed of broiler chickens has led to an increase in live weight and ADG. This is in line with the results found by Badr et al [20], who found an improvement in weight performance due to the substitution of maize by FB envelopes of 5-15% in Cobb broilers. However, Moula et al [19] for a 5% and 10% incorporation of FB cladodes in the broiler feed, observed no signi cant effect on body weight and ADG, in contrast to Ragab [26] who found in Hy-Line W-36 cocks fed with FB envelopes, a non-signi cant effect on body weight at 70 days but a positive effect on ADG.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The incorporation of FB g seed husks and seed cakes at a rate of 10% and 20% in the feed of broiler chickens has led to an increase in live weight and ADG. This is in line with the results found by Badr et al [20], who found an improvement in weight performance due to the substitution of maize by FB envelopes of 5-15% in Cobb broilers. However, Moula et al [19] for a 5% and 10% incorporation of FB cladodes in the broiler feed, observed no signi cant effect on body weight and ADG, in contrast to Ragab [26] who found in Hy-Line W-36 cocks fed with FB envelopes, a non-signi cant effect on body weight at 70 days but a positive effect on ADG.…”
Section: Discussionsupporting
confidence: 93%
“…The incorporation of the by-product of prickly pear processing (husks) and the by-product of oil extraction from BF seeds (oilcake) did not cause mortality in the experimental groups as reported by Badr et al [20] in Cobb chickens fed BF husks and Bakr et al [25] in rabbits fed BF zest. However, Moula et al [19], on broilers fed with 10% prickly pear cladodes in the diet, found a mortality rate of 10%, while Ragab [21] found a mortality rate of 3.3% in quails fed on diets containing 15% prickly pear shells.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations